Hormonal evaluation of infertile women in Border Guard Hospital, Peelkhana, Dhaka - Shapla, Nahid Reaz; Chowdhury, Liza; Khan, Rokeya; Nabi, Syed Nurun; Sultana, Sharmeen; Parveen, Zinia (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Infertility is very often observed in women. It is the failure to conceive after one year of regular unprotected coitus. Data from population based studies suggest that 10-15% couples in the western world experience infertility. Infertility can be caused by a number of factors. Hormonal problems are amongst the important factors contributing to female infertility. Aim: The aim of this study was to ascertain the FSH(Follicle Stimulating Hormone), LH(Leuteinizing Hormone), Prolactin, Testosterone, FT3(Free Triiodothyronine), FT4(Free Thyroxine), TSH(Thyroid Stimulating Hormone) and Oestradiol levels in infertile women. Methods: This observational study was carried out over a period of 1 year from June 2012 to May 2013 on 110 infertile women who reported to Gynae OPD(Out-Patient Department) in Border Guard Hospital, Dhaka. Blood samples of the subjects were taken on 2nd day of menstruation of regular menstrual cycle and on first visit of women having irregular menstrual cycle. Different hormonal studies were done by IMMULITE immunoassay. Semen analyses of their husbands were found to be normal. The results obtained were compared with the reference levels. Results: Among 110 infertile women, 86.37% cases were of primary infertility and 13.63% were 34 JAFMC Bangladesh. Vol 10, No 1 (June) 2014 of secondary infertility. In this study on infertile women majority (34.54%) of the cases of infertility were having PCODs(Polycystic Ovary Disease), others were of hypothyroidism (23.6%) and hyperprolactinaemia was found in 19.09% cases. Both PCODs and hypothyroidism were found in 6.36% cases and no abnormality was detected in 16.36% cases. The Mean ± SD of different hormonal levels were: FSH 2.58±1.63, LH 10.20±4.36, prolactin 61.17±1158 and testosterone 140±34.22 respectively. The mean ± SD of measured hormone levels were compared with reference levels of different hormones by using student t test. In case of FSH, LH, TSH, prolactin, testosterone, FT4 and Oestradiol the difference were statistically significant (P<0.01) but for FT3 was not statistically significant. Conclusion: In this study, PCOD was found to be the most common cause of infertility and other causes found were hyperprolactinaemia and hypothyroidism. DOI: http://dx.doi.org/10.3329/jafmc.v10i1.22902 Journal of Armed Forces Medical College Bangladesh Vol.10(1) 2014